Major nutrient contents and their uptake by brinjal as influenced by phosphorus and sulphur - Hasan, MM; Chowdhury, MAH; Saha, BK; Islam, MR (Journal of the Bangladesh Agricultural University, 2014)
A pot experiment was conducted in the net house of the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh to evaluate the influence of phosphorus (P) and sulphur (S) on major nutrient contents and their uptake by brinjal (cv. BARI brinjal-8) during the period from October, 2011 to May, 2012. The experiment was laid out in a completely randomized design with 12 treatments and 3 replications using four levels of P (0, 30, 60 and 90 kg P ha-1) and three levels of S (0, 15 and 30 kg S ha-1) along with the basal doses of urea, muriate of potash, boric acid, zinc oxide, cowdung and poultry manure. The study revealed that major nutrient contents and their uptake were significantly influenced by P and S interactions. They had positive significant effects on major nutrient contents and their uptake. Application of P increased N, P, K, Ca, Mg and S contents and their uptake upto 60 kg ha-1 and over the dose the values were reduced or near to control treatment. Similarly, the gradual increases of major nutrient contents and their uptake were found in S application upto 30 kg ha-1. Among the treatments the combination of P @ 60 kg ha-1 and S @ 30 kg ha-1 showed the highest N, P, K, S, Ca and Mg contents and their uptake. The lowest values were found in control treatment. Results showed that an appropriate interaction of P and S increased major nutrient contents of brinjal. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18206 J. Bangladesh Agril. Univ. 11(1): 41-46, 2013